Chromosome painting of telomeric repeats reveals new evidence for genome evolution in peanut - Pei DU; Li-na LI; Zhong-xin ZHANG; Hua LIU; Li QIN; Bing-yan HUANG; Wen-zhao DONG; Feng-shou TANG; Zeng-jun QI; Xin-you ZHANG (Journal of Integrative Agriculture)
Interspecific hybridization is an important approach to improve cultivated peanut varieties. Cytological markers such as tandem repeats will facilitate alien gene introgression in peanut. Telomeric repeats have also been frequently used in chromosome research. Most plant telomeric repeats are (TTTAGGG)n that are mainly distributed at the chromosome ends, although interstitial telomeric repeats (ITRs) are also commonly identified. In this study, the telomeric repeat was chromosomally localized in 10 Arachis species through sequential GISH (genomic in situ hybridization) and FISH (fluorescence in situ hybridization) combined with 4’,6-diamidino-2-phenylindole (DAPI) staining. Six ITRs were identified such as in the centromeric region of chromosome Bi5 in Arachis ipaënsis, pericentromeric regions of chromosomes As5 in A. stenosperma, Bho7 in A. hoehnei and Av5 in A. villosa, nucleolar organizer regions of chromosomes As3 in A. stenosperma and Adi3 in A. diogoi, subtelomeric regions of chromosomes Bho9 in A. hoehnei and Adu7 in A. duranensis, and telomeric region of chromosome Es7 in A. stenophylla. The distributions of the telomeric repeat, 5S rDNA, 45S rDNA and DAPI staining pattern provided not only ways of distinguishing different chromosomes, but also karyotypes with a higher resolution that could be used in evolutionary genome research. The distribution of telomeric repeats, 5S rDNA and 45S rDNA sites in this study, along with inversions detected on the long arms of chromosomes Kb10 and Bho10, indicated frequent chromosomal rearrangements during evolution of Arachis species.